Thermal properties of linear-low density polyethylene (LLDPE)/soya spent powder blends with the addition of epoxidised natural rubber - Sam, Sung Ting, Dr. (Trans Tech Publications, 2014)
Link to publisher's homepage at http://www.ttp.net/